CSP-based resource allocation model and algorithms for energy-efficient cloud computing - Wei-wei LIN; Bo LIU; Liang-chang ZHU; De-yu QI (Tongxin xuebao)
The resource allocation for energy-efficient cloud computing in a heterogeneous environment was modeled as a constraint satisfaction problem (CSP).By solving the constraint satisfaction problem,the optimized allocation scheme minimizing energy consumption in virtualized cloud data centers was obtained.Based on the optimized allocation scheme,an energy-efficient resource allocation algorithm,dynamicpower (DY),which takes into account the heterogene-ity of resources,was proposed.The performance of algorithm was evaluated using Choco.Experimental results show that,compared with first-fit decreasing (FFD),best-fit decreasing (BFD) and minimizing the number of physical machines (MinPM),the proposed algorithm (DY) has less energy consumption.